(untitled) (Health and Biosciences, 2023)
Tuberculosis is a disease caused by Mycobacterium tuberculosis, transmitted mainly through the air and can affect various organs of the body. Confirmation is performed by analyzing the lesion material, identifying Koch’s bacillus. Cross-sectional and descriptive study that evaluated the incidence rates calculated from the cases of tuberculosis notified, through the Information System of Notifiable Diseases (SINAN), between the years 2015 and 2020 in the municipalities of the State of Espírito Santo. According to the method described, 8,688 cases were observed in the chosen time frame, of which 71.06% are male and analyzing possible aggravating factors such as smoking and alcohol consumption, with high incidence rates in municipalities that make up the Metropolitan Region of Vitória, when compared to other municipalities in the state. It was determined that the age group with the highest incidence was 29 to 39 years old. The study, based on its results, has the potential to support discussions about disease control in the State, in addition to notification. In this way, it can be used to help public health management to optimize resources and teams for tuberculosis control in municipalities that present discrepant incidences to what was being proposed in relation to the Espírito Santo State TB Control Plan.